1989
DOI: 10.1007/bf01967295
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins in inflammatory bone pathology: Mechanism and therapeutic benefit of etodolac

Abstract: To investigate the role of PGE2 in the development of bone and joint pathology in rat adjuvant arthritis, hindlimb paws were evaluated by calcified tissue histologic techniques focusing on histochemical visualization of cartilage and bone lesions. Case studies of hindlimbs from normal, adjuvant arthritic, and etodolac-treated arthritic rats demonstrated the association of disease severity with inflammation, chondromalacia, replacement of adipose bone marrow with a fibroid marrow, osteoclastic bone resorption, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Histopathological findings of the nondecalcified tarsus with ankle, intertarsal and tarsometatarsal joints showed that 56% of arthritic rats developed severe and 44% moderate arthritis on day 28 after immunization. All animals had synovitis and inflammatory articular lesions in the joint regions and excessive bone resorption and proliferative new bone formation, as has also been described by others [1,2,[19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Histopathological findings of the nondecalcified tarsus with ankle, intertarsal and tarsometatarsal joints showed that 56% of arthritic rats developed severe and 44% moderate arthritis on day 28 after immunization. All animals had synovitis and inflammatory articular lesions in the joint regions and excessive bone resorption and proliferative new bone formation, as has also been described by others [1,2,[19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 51%
“…The sections (5 m thick) were stained using the Masson-Goldner trichrome method and the von Kossa method with hematoxylin/McNeal's tetrachrome counterstain [18]. Based upon histological studies in adjuvant arthritis [2,[19][20][21][22], a modified scoring system of hindpaws with a scale from 1 to 75 was used. This system allows differentiation of the severity of the changes, and is described in detail in our previous study [9].…”
Section: Histopathological Evaluationmentioning
confidence: 99%
“…Development of secondary swelling coincides with prostaglandin E 2 (PGE 2 ) production associated with the upregulation of PGHS-2 mRNA and protein in arthritic paw, but with little upregulation of PGHS-1 [15]. Furthermore, large amounts of PGE 2 are released from PGHS-2 expressing synovial tissue [15][16][17] and PGE 2 is responsible for the increase in bone resorption in the chronic stage of adjuvant-induced arthritis rats [18]. It has been also reported that PGE 2 itself induces PGHS-2 mRNA expression and PGE 2 production in cultured bone [19], and IL-1b stimulates osteoclast-like cell formation from bone marrow cells via PGE 2 production by a PGHS-2-dependent mechanism [20].…”
Section: Discussionmentioning
confidence: 99%